The Newborn Baby Ceremony in Labuhan Batu, South Aceh - Halimahtu Saddiah; Tiarnita Maria Sarjani Br. Siregar; Dinda Nurul Fadillah; Marchel Nathanael Sipahutar; M. Rafif Zaki Ramadhan (Ravine Publisher, 2024)
In the Acehnese community, childbirth holds sacred significance. This sacredness is reflected in specific rituals to introduce a newborn to the world. These rituals are seen as both a continuation of the Prophet Muhammad's actions and a way to maintain communication and exchange across generations. The rituals not only honor the birthing process but also provide physical and mental support to the mother after childbirth. This study focuses on the specific ritual of bathing a newborn baby, practised in the village of Blangporoh, South Aceh. Using interviews and field observations, the study reveals that this ritual continues to serve as a symbolic gesture of welcoming and integrating the baby into society. Additionally, the tradition of animal sacrifice (Akikah) often accompanies the bathing ritual. The sacrifice (akikah) for